Hardening components and hardening agents
Patent Information
- Application Number
- JP2025059762
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
Smart Images

Figure 2026166669000001 
Figure 2026166669000002 
Figure 2026166669000003
Abstract
Description
[Technical Field]
[0001] This invention relates to a curable composition having thermal decomposition properties and a cured product thereof. [Background technology]
[0002] Disassemblable adhesives are known in which the adhesive strength of the bonded parts decreases when subjected to stimuli such as heating, allowing the bonded parts to be easily separated. In recent years, the development of disassemblable adhesives has been progressing from the perspective of efficient use of resources and recycling.
[0003] Patent Document 1 describes a method for obtaining a heat-decomposable adhesive that has sufficient adhesive strength when bonded, but whose adhesive strength decreases when heated, making it easy to disassemble, by combining a moisture-crosslinkable polymer and heat-expandable particles. [Prior art documents] [Patent Documents]
[0004] [Patent Document 1] International Publication No. 2024 / 132795 [Overview of the project] [Problems that the invention aims to solve]
[0005] In the disassemblable adhesive disclosed in Patent Document 1, heating to a high temperature of 200°C is required to significantly reduce the adhesive strength. Since being able to disassemble at a lower temperature range offers advantages in terms of energy efficiency, this research aims to obtain an adhesive that can be disassembled at around 150°C. [Means for solving the problem]
[0006] [1] A heat-decomposable curable composition comprising (A) a polyoxyalkylene polymer having reactive silicon groups, and (B) heat-expandable particles, wherein the polymer (A) has a linear main chain structure and a number average molecular weight of 12,000 or more, the average particle diameter of the heat-expandable particles (B) is 12 μm or more, and the content of the heat-expandable particles (B) is 5 parts by weight or more per 100 parts by weight of the polymer (A). [2] The curable composition according to [1], wherein the content of the thermally expandable particles (B) is 80 parts by weight or less per 100 parts by weight of the polymer (A). [3] The curable composition according to [1], wherein the number average molecular weight of the polymer (A) is 50,000 or less. [4] The curable composition according to [1], wherein the average particle size of the thermally expandable particles (B) is 60 μm or less. A cured product obtained by curing any one of the curable compositions described in [5][1] to [4]. [Effects of the Invention]
[0007] According to the present invention, a curable composition and a cured product thereof that have excellent thermal decomposition properties in a temperature range of about 150°C are provided. [Modes for carrying out the invention]
[0008] <Overview> The curable composition of the present invention contains (A) a polyoxyalkylene polymer having reactive silicon groups (hereinafter sometimes simply referred to as "polymer (A)") and (B) unexpanded thermal expandable particles (hereinafter sometimes simply referred to as "thermal expandable particles (B)" unless otherwise specified).
[0009] The curable composition of the present invention can be suitably used as an adhesive for bonding parts of various industrial products, such as automobiles, building materials, and electrical and electronic equipment. Specific methods for using the curable composition of the present invention as an adhesive are as follows.
[0010] (1) Adhesion process The curable composition is cured to bond the components together. Polymer (A) forms a crosslinked structure through hydrolysis and condensation between reactive silicon groups, causing the curable composition to harden and become a cured product. Hydrolysis and condensation between reactive silicon groups proceed, for example, due to moisture in the air.
[0011] (2) Demolition process When a product obtained by bonding components together becomes unnecessary, the components are separated by heating. Heating increases the volume of the thermally expandable particles (B), making the hardened material brittle, thus allowing the components to be easily separated.
[0012] The curable composition of the present invention exhibits excellent thermal decomposition properties, particularly because the polymer (A) has a linear main chain structure and a number-average molecular weight of 12,000 or more, and the content of thermally expandable particles (B) with an average particle diameter of 12 μm or more is 5 parts by weight or more per 100 parts by weight of the total polymer (A).
[0013] <Polymer (A)> Polymer (A) has reactive silicon groups and comprises a main chain structure and terminal structures bonded to the main chain structure. The main chain structure is a structure in which multiple constituent units derived from monomers are continuously bonded together. There may be one type of monomer or multiple types. The main chain structure of polymer (A) may be linear or branched, but the main chain structure of polymer (A) in which the effects of the present invention are exhibited is linear. The terminal structure refers to the part located at the end of polymer (A), and means a part other than the main chain structure.
[0014] Reactive silicon groups can be present in the main chain structure and in the terminal structures. Furthermore, two or more reactive silicon groups may be present in a single terminal structure. In polymer (A), it is preferable that reactive silicon groups be present in the terminal structures because they readily react with moisture during the bonding process.
[0015] The reactive silicon group is not particularly limited as long as it is a silicon-containing group having a silanol group or a silicon-containing group capable of forming a silanol group by hydrolysis, and may be various known reactive silicon groups. When the reactive silicon group forms a silanol group, the polymer (A) is crosslinked by a condensation reaction between the silanol groups.
[0016] As the reactive silicon group, a group represented by the following formula (1) is preferable. -SiR 1 a X 3-a (1) In formula (1), R 1 each independently represents a substituted or unsubstituted hydrocarbon group having 1 to 20 carbon atoms, or a triorganosiloxy group represented by R 0 ₃SiO-. In the triorganosiloxy group, the three R 0 each independently represent a hydrocarbon group having 1 to 20 carbon atoms. The three R 0 may be the same or different. Each X is independently a hydroxy group or a hydrolyzable group. a is 0, 1 or 2.
[0017] R in formula (1) 1 is preferably an alkyl group and an aryl group, more preferably a methyl group, an ethyl group and a phenyl group, still more preferably a methyl group and an ethyl group, and particularly preferably a methyl group. When a plurality of R 1 are present in formula (1), the plurality of R 1 may be the same group, or may be a combination of two or more different groups.
[0018] The hydrolyzable group is not particularly limited, and may be a known hydrolyzable group. The hydrolyzable group is preferably an alkoxy group, an acyloxy group, a ketoximate group and an alkenyloxy group. An alkoxy group such as a methoxy group and an ethoxy group is more preferable because of its mild hydrolyzability and easy handling. The methoxy group is particularly preferable in that the curability of the curable composition can be easily adjusted.
[0019] The reactive silicon group represented by formula (1) is not particularly limited, but dimethoxymethylsilyl and trimethoxysilyl groups are preferred because they facilitate the synthesis of polymer (A). Trimethoxysilyl and methoxymethyldimethoxysilyl groups are preferred for their excellent curability. Dimethoxymethylsilyl groups are particularly preferred for their excellent stability.
[0020] The main chain structure of polymer (A) contains constituent units derived from oxyalkylene. Specific examples of oxyalkylene include ethers such as oxyethylene, oxypropylene, oxybutylene, and oxytetramethylene. The oxyalkylene may also be a combination such as oxyethylene-oxypropylene or oxypropylene-oxybutylene.
[0021] Polyoxypropylene is particularly preferred as the main chain structure of polymer (A). Polymer (A) with a polyoxypropylene main chain structure is amorphous and has relatively low viscosity, and the cured product tends to have excellent adhesion.
[0022] The ratio of oxyalkylene-derived constituent units to the total amount of constituent units in the main chain structure of polymer (A) is 50 mol% or more. The main chain structure of polymer (A) may contain other bonds besides ether bonds (urethane bonds, urea bonds, etc.), but from the viewpoint of obtaining a curable composition with excellent storage stability and workability, the ratio of oxyalkylene-derived constituent units to the total amount of constituent units in the main chain structure of polymer (A) is, for example, 60 mol% or more, 70 mol% or less, 80 mol% or more, 90 mol% or more, 99 mol% or more, or 100 mol%.
[0023] The method for synthesizing the main chain structure of polymer (A) is not particularly limited, and known synthesis methods may be used. Polyoxyalkylene polymers can be obtained, for example, by a ring-opening polymerization reaction of a cyclic ether compound using a polymerization catalyst in the presence of an initiator. Polymerization using a complex metal cyanide catalyst (see Japanese Patent Publication No. 46-27250, U.S. Patent No. 3278457, etc.) is particularly preferred due to its low manufacturing cost and the ability to obtain polymers with a narrow molecular weight distribution.
[0024] The method for introducing reactive silicon groups into the main chain structure of polymer (A) is not particularly limited and may be a known method. One example of a known method is to convert the terminal hydroxyl groups of a hydroxyl-terminated organic polymer into carbon-carbon unsaturated groups, and then to the carbon-carbon unsaturated groups, HSiR 1 a X 3-a One method is hydrosilylation using a hydrosilane represented by R. 1 X and a are the same as those in equation (1), respectively.
[0025] The number-average molecular weight (Mn) of polymer (A), as polystyrene-equivalent molecular weight in GPC (gel permeation chromatography), is preferably 800 to 100,000, more preferably 1,500 to 50,000, and particularly preferably 2,000 to 30,000. The weight-average molecular weight (Mw) of polymer (A), as polystyrene-equivalent molecular weight in GPC, is preferably 1,000 to 110,000, more preferably 2,000 to 55,000, and particularly preferably 2,400 to 33,000.
[0026] Specific examples of commercially available polymers (A) include various reactive silicon group-containing polyoxypropylene products such as Kaneka MS Polymer (registered trademark) and Kaneka Cyril (registered trademark). All of these commercially available polymers (A) are products of Kaneka Corporation. In addition, AGC Inc.'s Exester (registered trademark), WACKER's GENIOSIL (registered trademark), and RISUN POLYMER's STP can also be used as polymers (A).
[0027] The polymer (A) that can be used in the present invention preferably has a number average molecular weight of 12,000 or more. The lower limit of the number average molecular weight of polymer (A) is, for example, 14,000 or more, 15,000 or more, 16,000 or more, 18,000 or more, or 20,000 or more, and the upper limit is, for example, 50,000 or less, 45,000 or less, 40,000 or less, or 35,000 or less. If the number-average molecular weight of polymer (A) is less than 12,000, adding the following thermally expandable particles (B) will result in a certain degree of decomposition, but it is not suitable for decomposition at temperatures around 150°C. When polymer (A) with a number-average molecular weight of less than 12,000 is used, the cured composition shows high strength, but its elongation is small, so in order to obtain sufficient decomposition, it is necessary to process it at a high temperature of around 200°C or to add a large amount of thermally expandable particles (B). On the other hand, polymer (A), which has a number-average molecular weight exceeding 50,000, exhibits high elongation, but is not thought to show sufficient strength in the composition state before decomposition after curing.
[0028] <Thermally expandable particles (B)> Thermally expandable particles (B) are particles that have the property of expanding when heated. Preferably, thermally expandable particles (B) are thermally expandable microcapsules. Thermally expandable microcapsules are tiny hollow particles in which a volatile expanding agent, such as a low-boiling point solvent, is encapsulated inside an outer shell. When thermally expandable particles (B) are heated, the outer shell softens and the encapsulated volatile substance volatilizes, causing the outer shell to expand due to the resulting pressure, thereby increasing the particle volume.
[0029] The outer shell of the thermally expandable microcapsules is preferably formed from a thermoplastic resin. Examples of thermoplastic resins include vinyl polymers and copolymers thereof such as ethylene, styrene, vinyl acetate, vinyl chloride, vinylidene chloride, acrylonitrile, methacrylonitrile, butadiene, and chloroprene; polyamides such as nylon 6 and nylon 66; and polyesters such as polyethylene terephthalate. Acrylonitrile copolymers are preferred because they are less permeable to the encapsulated volatile substances.
[0030] Examples of volatile substances encapsulated inside thermally expandable microcapsules include C3-C8 hydrocarbons such as propane, propylene, butene, n-butane, isobutane, isopentane, neopentane, n-pentane, hexane, heptane, octane, and isooctane; methane halides such as methyl chloride and methylene chloride; chlorofluorocarbons such as CCl3F and CCl2F2; tetraalkylsilanes such as tetramethylsilane and trimethylethylsilane; and low-boiling point liquids such as petroleum ethers.
[0031] As the thermally expandable particles (B), commercially available products can also be used. Examples of commercially available products include Nouryon's microspheres (product names: Expansion 051 DU 40, Expansion 043 DU 80, Expansion 920 DU 20), Matsumoto Oil & Fat Pharmaceutical's microspheres (product names: F-20D, F-30D, F-40D, FN-100D, FN-100MD, FN-100SD, FN-100SSD, FN-180D, FN-180SD, FN-180SSD, F-190D, F-260D), and Kureha's microspheres (product names: H850D, H880D, S2340D, S2640D).
[0032] The lower limit of the expansion initiation temperature for the thermally expandable particle (B) that can be used in the present invention is, for example, 70°C or higher, 90°C or higher, 100°C or higher, or 110°C or higher, and the upper limit of the expansion initiation temperature is, for example, 180°C or lower, 170°C or lower, 160°C or lower, or 150°C or lower. In this specification, the expansion onset temperature refers to the temperature at which the expansion curve (a graph with temperature on the horizontal axis and particle volume on the vertical axis) begins to rise (the particle volume begins to increase) when an unexpanded thermally expandable particle (B) is heated at a rate of 20°C per minute. This expansion curve is obtained by TMA (Thermomechanical Analysis) measurement. It is preferable that the expansion onset temperature of the thermally expandable particle (B) is 70°C or higher, because the thermally expandable particle (B) does not expand when curing the curable composition, but expands when heated during dismantling. On the other hand, since there is a need for dismantling adhesives to be able to be dismantled at temperatures lower than 200°C, it is preferable that the expansion onset temperature of the thermally expandable particle (B) is 180°C or lower.
[0033] The average particle size of the thermally expandable particles (B) is the median diameter (D(0.5)) measured by low-angle laser light scattering. The lower limit of the thermally expandable particle (B) used in the present invention is, for example, 9 μm or more, 12 μm or more, 15 μm or more, or 18 μm or more, and the upper limit is, for example, 60 μm or less, 55 μm or less, 50 μm or less, 45 μm or less, 40 μm or less, 35 μm or less, or 30 μm or less. If the average particle size of the thermally expandable particles (B) is too small or too large, sufficient thermal decomposition may not be obtained. Conversely, if the average particle size of the thermally expandable particles (B) is too large, sufficient adhesive strength may not be obtained as an adhesive. The average particle size of the thermally expandable particles (B) is preferably, for example, 9 to 30 μm, 9 to 25 μm, or 9 to 24 μm. When the average particle size of the thermally expandable particles (B) is within the above range, the thermal decomposition of the curable composition is good.
[0034] The lower limit of the content of the thermally expandable particles (B) used in the present invention is, for example, 5 parts by weight or more, 10 parts by weight or more, 15 parts by weight or more, or 20 parts by weight or more, per 100 parts by weight of the total polymer (A), and the upper limit is 80 parts by weight or less, 70 parts by weight or less, 60 parts by weight or less, 55 parts by weight or less, or 50 parts by weight or less. When the content of thermally expandable particles (B) is 5 parts by weight or more per 100 parts by weight of polymer (A), the thermal decomposition properties of the curable composition are good. This is thought to be because, when the content of thermally expandable particles (B) is equal to or greater than the above value, the size of the thermally expandable particles (B) in the curable composition is sufficient to generate the stress necessary for decomposition inside the cured material. Furthermore, if the content of thermally expandable particles (B) is too high, the adhesive strength may be insufficient.
[0035] <Additives> The curable composition may contain additives in addition to the polymer (A) and the thermally expandable particles (B). Examples of additives include curing catalysts, fillers, adhesion promoters, plasticizers, solvents, diluents, thixotropic agents, antioxidants, light stabilizers, UV absorbers, property modifiers, tackifying resins, compounds containing epoxy groups, photocurable substances, oxygen-curable substances, epoxy resins and other resins, surface modifiers, foaming agents, curing modifiers, flame retardants, silicates, radical inhibitors, metal deactivators, phosphorus-based peroxide decomposers, lubricants, pigments, and antifungal agents.
[0036] Preparation of curable compositions The curable composition can be prepared as a one-component type, where all components are pre-mixed and sealed for storage, and then cured by moisture in the air after application. Alternatively, it can be prepared as a two-component type, where components such as a curing catalyst, filler, plasticizer, and water are mixed separately, and the mixture containing these components is mixed with the curable composition containing a polyoxyalkylene polymer (A) and thermally expandable particles (B) before use. The one-component type is preferred in terms of workability.
[0037] Uses of curable compositions The curable composition can be suitably used as an adhesive for bonding parts of various industrial products, such as automobiles, building materials, and electrical and electronic equipment. As mentioned above, the curable composition has excellent thermal decomposition properties, so by using the curable composition as an adhesive, parts can be easily separated and disassembled by heating when recycling products or when re-bonding parts. The curable composition may also be used as a sealant. [Examples]
[0038] Examples and comparative examples are given below for further explanation. (Materials used in the preparation of the cured composition) Plasticizer: Diisodecyl phthalate (manufactured by J-Plus Co., Ltd., product name: DINP) Filler: Heavy calcium carbonate (GCC) (manufactured by Shiraishi Kogyo Co., Ltd., product name: Whiteon SB Red) Precipitated calcium carbonate (PCC) (manufactured by Shiraishi Kogyo Co., Ltd., product name: Shirotsuya CCR) Coloring agent: Titanium dioxide (manufactured by Ishihara Sangyo Co., Ltd., product name: Typeque R-820) Thixotropic agent (manufactured by Kusumoto Chemical Co., Ltd., product name: Disparon 6500) UV absorber: Benzotriazole-based UV absorber (manufactured by BASF Japan Ltd., product name: Chinuvin 326) Light stabilizer: Hindered amine light stabilizer (manufactured by BASF Japan Ltd., product name: Tinuvin 770DF) Antioxidant: Hindered phenol antioxidant (manufactured by BASF Japan Ltd., product name: Irganox 245) Dehydrating agent: Vinyltrimethoxysilane (manufactured by Evonik, product name: Dynasylan VTMO) Adhesion-enhancing agent: γ-(2-aminoethyl)aminopropyltrimethoxysilane (manufactured by Evonik, trade name: Dynasylan DAMO) Curing catalyst: Dibutyltin bisacetylacetonate (manufactured by Nitto Chemical Co., Ltd., product name: Neostan U-220H)
[0039] (molecular weight measurement) The number-average molecular weight Mn and weight-average molecular weight Mw were measured by GPC under the following conditions. Liquid delivery system: Tosoh HLC-8420GPC Column: Tosoh TSKgel SuperH series Solvent: THF Molecular weight: Polystyrene equivalent Measurement temperature: 40℃
[0040] (Calculation of the average number of reactive silicon groups) The average number of reactive silicon groups per molecule of the polymer was calculated by NMR measurement.
[0041] [Synthesis of polyoxyalkylene polymers containing reactive silicon groups] <Synthesis of polymer (A1)> Using polyoxypropylene glycol with a number-average molecular weight of approximately 4,500 as an initiator, propylene oxide was polymerized with a zinc hexacyanocobaltate-grime complex catalyst to obtain polyoxypropylene (P-1) with a number-average molecular weight of 27,900 (end-group equivalent molecular weight of 17,700) and a molecular weight distribution Mw / Mn = 1.21, having hydroxyl groups at both ends. Subsequently, 1.2 molar equivalents of sodium methoxide in a 28% methanol solution were added to the hydroxyl groups of this hydroxyl-terminated polyoxypropylene (P-1). After removing methanol by vacuum defloration, 1.5 molar equivalents of allyl chloride were further added to the hydroxyl groups of the polymer (P-1) to convert the terminal hydroxyl groups to allyl groups, and the unreacted allyl chloride was removed by vacuum defloration. After mixing and stirring n-hexane and water with the obtained unpurified polyoxypropylene, the water was removed by centrifugation, and the metal salts in the polymer were removed by vacuum defloration of the hexane from the resulting hexane solution. From the above steps, polyoxypropylene (Q-1) having allyl groups at its termini was obtained. To 500 g of this polymer (Q-1), 50 μL of platinum divinyldisiloxane complex solution (3% by weight isopropanol solution in terms of platinum) was added, and 4.8 g of dimethoxymethylsilane was slowly added dropwise while stirring. After reacting the mixed solution at 100°C for 2 hours, the unreacted dimethoxymethylsilane was removed under reduced pressure to obtain polyoxypropylene (A1) with a number average molecular weight of approximately 28,500 and dimethoxymethylsilyl groups at its termini. Polymer (A1) was found to have an average of 0.8 dimethoxymethylsilyl groups at each termini and an average of 1.6 dimethoxymethylsilyl groups per molecule.
[0042] <Synthesis of polymer (A2)> Using polyoxypropylene glycol with a number-average molecular weight of approximately 4,500 as an initiator, propylene oxide was polymerized with a zinc hexacyanocobaltate-grime complex catalyst to obtain polyoxypropylene (P-2) with a number-average molecular weight of 16,200 (end-group equivalent molecular weight of 10,200) and a molecular weight distribution Mw / Mn = 1.23, having hydroxyl groups at both ends. Subsequently, 1.2 molar equivalents of sodium methoxide in a 28% methanol solution were added to the hydroxyl groups of this hydroxyl-terminated polyoxypropylene (P-2). After removing methanol by vacuum defloration, an additional 1.5 molar equivalents of allyl chloride were added to the hydroxyl groups of the polymer (P-2) to convert the terminal hydroxyl groups to allyl groups, and the unreacted allyl chloride was removed by vacuum defloration. To the obtained unpurified polyoxypropylene, n-hexane and water were mixed and stirred, and the water was removed by centrifugation. The metal salts in the polymer were removed by vacuum defloration of the hexane from the resulting hexane solution. From the above steps, polyoxypropylene (Q-2) having allyl groups at its termini was obtained. To 500 g of this polymer (Q-2), 50 μL of platinum divinyldisiloxane complex solution (3% by weight isopropanol solution in terms of platinum) was added, and 6.5 g of dimethoxymethylsilane was slowly added dropwise while stirring. After reacting the mixed solution at 100°C for 2 hours, the unreacted dimethoxymethylsilane was removed under reduced pressure to obtain polyoxypropylene (A2) with dimethoxymethylsilyl groups at its termini and a number-average molecular weight of approximately 16,200. Polymer (A2) was found to have an average of 0.6 dimethoxymethylsilyl groups at each termini and an average of 1.2 dimethoxymethylsilyl groups per molecule. <Synthesis of polymer (A3)> Using a polyoxypropylene triol with a number-average molecular weight of approximately 4,500 as an initiator, propylene oxide was polymerized with a zinc hexacyanocobaltate grime complex catalyst to obtain polyoxypropylene (P-3) with a number-average molecular weight of 24,600 (end-group equivalent molecular weight of 17,400) and a molecular weight distribution Mw / Mn = 1.31, with hydroxyl groups at the ends. 1.2 molar equivalents of sodium methoxide in a 28% methanol solution were added to the hydroxyl groups of the obtained hydroxyl-terminated polyoxypropylene (P-3). After removing methanol by vacuum defoliation, an additional 1.5 molar equivalents of allyl chloride were added to the hydroxyl groups of the polymer (P-3) to convert the terminal hydroxyl groups to allyl groups. Unreacted allyl chloride was removed by vacuum defoliation. The obtained unpurified polyoxypropylene was mixed and stirred with n-hexane and water, then the water was removed by centrifugation, and the metal salts in the polymer were removed by vacuum defoliation of the hexane from the resulting hexane solution. From the above steps, polyoxypropylene (Q-3) having allyl groups at its termini was obtained. To 500 g of this polymer (Q-3), 50 μl of platinum divinyldisiloxane complex solution (3% by weight isopropanol solution in terms of platinum) was added, and 6.4 g of dimethoxymethylsilane was slowly added dropwise while stirring. After reacting at 100°C for 2 hours, the unreacted dimethoxymethylsilane was removed under reduced pressure to obtain polyoxypropylene (A3) with dimethoxymethylsilyl groups at its termini and a number-average molecular weight of 26,200. Polymer (A3) was found to have an average of 0.7 dimethoxymethylsilyl groups at each termini and an average of 2.2 dimethoxymethylsilyl groups per molecule.
[0043] [Preparation of curable compositions] (Thermally expandable particles) The details of the unexpanded thermally expandable particles used in the following examples and comparative examples are as follows. (B-1): Manufactured by Nouryon, product name: Expansion 043 DU 80, average particle size D (0.5): 16~24 μm (measured by low-angle laser scattering method) (B-2): Manufactured by Nouryon, product name: Expansion 051 DU 40, average particle size D (0.5): 9~15 μm (measured by low-angle laser scattering method) (B-3): Manufactured by Nouryon, product name: Expansion 920 DU 20, average particle size D (0.5): 5~9 μm (measured by low-angle laser scattering method)
[0044] <Preparation of curable compositions for Examples 1-6 and Comparative Examples 1-3> According to the formulations described in Tables 1-3, polyoxyalkylene polymers (A1-3), diisodecyl phthalate, heavy calcium carbonate (GCC), precipitated calcium carbonate (PCC), titanium dioxide as a white pigment, a benzotriazole-based UV absorber as an anti-sagging agent and UV absorber, a hindered amine-based light stabilizer as a light stabilizer, and a hindered phenol-based antioxidant as an antioxidant were mixed and thoroughly kneaded, and physical dehydration was performed by stirring under reduced pressure at 120°C for 2 hours. After cooling to below 40°C, unexpanded thermally expandable particles (B1-3), vinyltrimethoxysilane as a dehydrating agent, γ-(2-aminoethyl)aminopropyltrimethoxysilane as an adhesion imparter, and dibutyltin bisacetylacetonate as a curing catalyst were added and kneaded to obtain a curable composition.
[0045] [evaluation] <Tensile shear strength> Aluminum plates were used as the adherends. At 23°C and 50% relative humidity, the curable compositions of Examples 1-6 and Comparative Examples 1-3 were applied to a 25mm x 12.5mm bonding surface on the surface of the aluminum plates to a thickness of 50μm. Two minutes after application, an aluminum plate without the curable composition was pressed onto the surface of the aluminum plate coated with the curable composition, thereby bonding the two aluminum plates together. The resulting test specimens were cured for 3 days at 50% relative humidity and then for 4 days at 50°C to prepare test pieces. Tensile shear strength tests were performed in an atmosphere of 23°C and 50% relative humidity, and the tensile shear strength (MPa) was measured. Hereafter, the shear strength measured here will be referred to as the "initial strength (MPa)". The measurement was performed using a Shimadzu Autograph (AGS-J) at a tensile speed of 50mm / min. Furthermore, the test specimens were placed in a constant temperature bath preheated to 150°C, removed after 30 minutes to allow them to return to room temperature, and then subjected to a tensile shear strength test in the same manner as described above, and the tensile shear strength (MPa) was measured. Hereafter, the shear strength measured here will be referred to as the "strength after heating (MPa)". The "rate of change in tensile shear strength (%)" was calculated by subtracting the initial strength from the strength after heating and dividing by the initial strength.
[0046] [Evaluation Results] Tables 1-3 show the compositions of Examples 1-6 and Comparative Examples 1-3, as well as the evaluation results of their tensile shear strength tests.
[0047] [Table 1]
[0048] When linear polymers (A-1 and A-2) were used, the rate of change in tensile shear strength after heating increased, but when branched polymer (A-3) was used, the rate of change in tensile shear strength after heating decreased, suggesting that it is unsuitable as a decomposable adhesive in the temperature range of around 150°C. Furthermore, even among the linear polymers, the decrease in strength after heating was more significant in polymer (A-1) with a number average molecular weight of 20,000 than in polymer (A-2) with a number average molecular weight of 10,000, indicating superior decomposability in the temperature range of around 150°C.
[0049] [Table 2]
[0050] For thermally expandable particles with an average particle size of 5-9 μm (B-3), the rate of change in peel strength after heating decreased, while for thermally expandable particles with an average particle size of 9 μm or more (B-1 and B-2), the rate of change in peel strength after heating increased. This suggests that thermally expandable particles with a particle size of 9 μm or more should be used for disassemblable adhesives in the temperature range of around 150°C.
[0051] [Table 3]
[0052] Adding 10 parts by weight or more of thermally expandable particles (B-1) to 100 parts by weight of polymer (A) resulted in a significant increase in the rate of change of tensile shear strength. On the other hand, the rate of change of tensile shear strength tended to decrease compared to when 50 parts by weight of thermally expandable particles (B-1) were added (Example 6) and when 30 parts by weight were added (Example 5) to 100 parts by weight of polymer (A). From this, it appears that adding more thermally expandable particles (B-1) is not necessarily better, and that the amount should generally be 80 parts by weight or less per 100 parts by weight of polymer (A).
Claims
1. (A) Polyoxyalkylene polymers having reactive silicon groups, and (B) Thermally expandable particles A heat-decomposable curable composition containing, The polymer (A) has a linear main chain structure and a number-average molecular weight of 12,000 or more. The average particle diameter of the thermally expandable particles (B) is 9 μm or more. A heat-decomposable, curable composition wherein the content of the heat-expandable particles (B) is 5 parts by weight or more per 100 parts by weight of the polymer (A).
2. The curable composition according to claim 1, wherein the content of the thermally expandable particles (B) is 80 parts by weight or less per 100 parts by weight of the polymer (A).
3. The curable composition according to claim 1, wherein the number average molecular weight of the polymer (A) is 50,000 or less.
4. The curable composition according to claim 1, wherein the average particle diameter of the thermally expandable particles (B) is 60 μm or less.
5. A cured product obtained by curing the curable composition according to any one of claims 1 to 4.
Citation Information
Patent Citations
Composition comprising a moisture-crosslinkable polymer
WO2024132795A1